(untitled) (Academia Science Repository, 2023)
In this article, the development of the professional competence of a modern pedagogue is focused on the effective use of methods and quality education, and in turn, on the professional skills of the pedagogue. In the article, the educational process has a special place, and the professional competence and skills of the modern pedagogue are highlighted scientifically.